EVALUASI KESESUAIAN ATP DAN MODUL AJAR MATEMATIKA DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMAN 1 PANTI - Khaidir, Christina; Aulia, Muthiah; Puti Asyifa, Aini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to evaluate the accuracy and alignment of the Learning Objectives Flow (ATP) and mathematics teaching modules based on the principles of the Merdeka Curriculum at SMAN 1 Panti, Pasaman Regency. A descriptive qualitative approach was used, with data collected through document analysis, classroom observations, and semi-structured interviews. The findings indicate that the ATP and teaching modules were systematically developed and align well with the Merdeka Curriculum's principles, particularly in terms of structure, learning objectives, and the integration of Pancasila Student Profile values. However, several shortcomings were identified, including limited use of digital media in teaching and the suboptimal implementation of differentiated instruction. While the modules contain essential components such as identity, material, learning activities, assessment, and student profiling, there is still a need for improvement in remedial and enrichment strategies. This study recommends enhancing the use of interactive digital tools and providing further training for teachers to design more contextual and student-centered learning materials. The results of this study are expected to serve as a foundation for further evaluation and development in the implementation of the Merdeka Curriculum.Keywords: Merdeka Curriculum, Learning Objectives Flow, Teaching Module, Mathematics, Senior High School